Accumulated and new case records of variants of concern of COVID-19, Brazil, 2021-2022: Ômicron, Gamma and Delta - Benito, Linconl Agudo Oliveira (2022)
Objective: To analyze the frequency of records of new and accumulated cases of variants of concern (VOC) of COVID-19, in “Brazil”, in the years “2021 and 2022”. Method: Exploratory, descriptive, comparative and quantitative research. Data were acquired from the Ministry of Health (MS). Results: A universe of 113,318 records was identified, with the highest preponderance consisting of accumulated cases with 95.2% (n=107,925) and the lowest of new cases with 4.8% (n=5,393). The VOC Ômicron recorded the highest preponderance, both of accumulated cases and of new cases, accounting for 40.3% (n=43,480) and 98.9% (n=5,334) respectively. VOC Gamma recorded the lowest preponderance with 24.7% (n=26,607) accumulated cases and 0.1% (n=4) new cases. Conclusion: There was an increase in the frequency of records of accumulated and new cases of Omicron, Delta and Gamma VOC of COVID-19, in the geographic and historical area analyzed.